A tradução para o português dos socioletos literários da trilogia Fundação, de Isaac Asimov - Silva Júnior, Nilfan Fernandes da (2021)
In general, among all the themes studied in Science Fiction, the translation of linguistic varieties is one of the less regarded by the literary criticism. These varieties play an important role to the internal verisimilitude in their fictional universes. The so called “literary sociolects” can express many attributes of a character, their values and attitudes, as theorized by the Canadian researcher Lane-Mercier (1997). This research is mainly focused on the linguistic varieties of Isaac Asimov’s Foundation trilogy (Foundation, Foundation and Empire, and Second Empire) - a futuristic science fiction classic. The trilogy tells the story of how the psychohistorian Hari Seldon, with his mathematical and sociological predictions, could foresee the fall of the Galactic Empires and stablish a Foundation at the end of the galaxy in order to assemble all human knowledge and thus try to contain its total collapse. Based on a qualitative comparison between American English and Brazilian Portuguese from the Foundation's trilogy, topics such as deviations from translation norms and some deforming tendencies proposed by Antoine Berman (2007) were discussed. Therefore, analyzes of the most notable literary sociolects were carried out, among which: the religious and scientific technolects, the rural dialect of Narovi, the idiolectal ambiguity of the Mule, and both eye dialects of Lord Dorwin and Homir Munn. As a research corpus, there were used the most recent translation into Portuguese of the Foundation trilogy (2009 - Aleph), by Fábio Fernandes and Marcelo Barbão. Finally, a more general discussion of languages and linguistic varieties in other works of Speculative Fiction was presented, focused on Science Fiction.